Apa itu Teologi yang Baik? - Billy Kristanto (Verbum Christi: Jurnal Teologi Reformed Injili, 2023)
Michael Welker describes nine levels that constitute theological normativity and weight so that theology can be called theology. Inspired by it, the author wants to share what makes a theology a good theology. The author explains seven aspects to be considered in developing a fruitful theology.